Enhanced dissociation of charge-transfer states in narrow band gap polymer:fullerene solar cells processed with 1,8-octanedithiol - Moet, D. J. D.; Lenes, M.; Morana, M.; Azimi, H.; Brabec, Christoph; Blom, P. W. M. (Applied Physics Letters, 2010)
The improved photovoltaic performance of narrow band gap polymer:fullerene solar cells processed from solutions containing small amounts of 1,8-octanedithiol is analyzed by modeling of the experimental photocurrent. In contrast to devices that are spin coated from pristine chlorobenzene, these cells do not produce a recombination-limited photocurrent. Modeling of the experimental data reveals that a sixfold reduction in the decay rate of photogenerated bound electron-hole pairs can account for the marked increase in short-circuit current density and fill factor. At short-circuit conditions, the dissociation probability of bound pairs is found to increase from 48% to 70%. © 2010 American Institute of Physics.